Expressional Alteration of Cytokeratins in Oral Leukoplakia and Oral Leukoplakia-associated Oral Squamous Cell Carcinoma: A Cross-sectional Study - Mehebuba Sultana; Pooja Lahiri; Mousumi Pal; Neha Shah; SK Abdul Mahmud; Jyotirmoy Chatterjee; Sanjeet Kr Das; Sangeeta Sinha (Journal of Clinical and Diagnostic Research)
Introduction: Oral Squamous Cell Carcinoma (OSCC) is characterised by high morbidity and poor survival rates, often developing from pre-existing Oral Potentially Malignant Disorders (OPMDs) like Oral Leukoplakia (OLKP). Early detection of a premalignant lesion can significantly increase survival rates. However, histopathological evaluation is unable to predict the potential for malignant transformation. This subjectivity has turned interest toward molecular markers, specifically Cytokeratins (CK), which may be essential in understanding the molecular changes occurring during the progression from OLKP to OSCC. Aim: The aim of this study is to examine the Haematoxylin (H) and Eosin (E) stained light microscopic features of Normal Oral Mucosa (NOM), OLKP, and OSCC. We will compare and corroborate, the expressions of CK 8/18 and CK 5/6 in NOM, OLKP, and OSCC, and assess their roles as potential biomarkers in malignant transformation. Materials and Methods: This cross-sectional study was conducted in the Department of Oral and Maxillofacial Pathology at Guru Nanak Institute of Dental Sciences and Research (GNIDSR), Kolkata, and the School of Medical Science and Technology (SMST), IIT, Kharagpur, West Bengal, India, from January 2019 to February 2020. The study included 26 cases of OLKP and OSCC, along with five cases of NOM. Histopathological and immunohistochemical evaluations (CK 8/18 and CK 5/6) were performed, measuring grey scale values using Image J software. Unpaired Student’s t-test and one-way ANOVA tests were applied to better understand the significant changes in grey scale values, with a set significance level of <0.05. Results: Out of total number participant, majority of them in both OLKP 9 (81%) and OSCC 12 (80%) patients were males. A considerable number of OLKP patients were in the age group of 51-60 years (35%), followed by the age range of 41-50 years (28%), 31-40 years (19%) and 61-70 years (18%), while in cases of OSCC-50% of patients were in the age group of 61-70 years, followed by the age range of 51-60 years (30%), 71-80 years (15%) and 41-50 years (5%). The staining intensity of both CK 5/6 and CK 8/18 significantly decreased (p-value <0.05) from basal to suprabasal and superficial layers in NOM and OLKP. Furthermore, a significant increase (p-value <0.05) in staining intensity was observed when comparing NOM vs. OLKP and NOM vs. OSCC. Conclusion: It can be suggested that the expressional alterations of CK 8/18 and CK 5/6, as well as their correlation in different layers of NOM and OLKP, can be considered potential biomarkers for better understanding the progression toward OSCC, as well as its prognosis.